DETERMINING ELDERLY-FRIENDLY FEATURES BASED ON AN AGE-FRIENDLY CITY APPROACH: AN EMPIRICAL ANALYSIS ON LOCAL PERSPECTIVE IN TAIPING AND IPOH, MALAYSIA - Rashid, Kushairi; Mohamed, Thuraiya; Azyze Ellah Azyze, Siti Norhawa; Ismail, Hafiszah (PLANNING MALAYSIA, 2022)
The elderly come from diverse backgrounds and experiences. Thus, they need strategies that can assist them in cherishing a pleasant and respected life, especially in the city. However, the state of age-friendly and elderly-friendly remains a subject for exploration, especially in Malaysia. This study was conducted to determine critical elderly-friendly city features and propose quickwin strategies to adapt Malaysian cities with ageing populations. The study primarily aims to develop an age-friendly city framework consisting of key city features based on Malaysia's local perspective. Quantitative deductive research applied structured surveys as the primary research strategy. Ipoh and Taiping, two cities with the highest elderly in Malaysia, were selected for the study. The Confirmatory Factor Analyses identified 24 key features as necessary, therefore considered to form the Malaysia Cities for Ageing Population Framework (MCAP). It endeavours that the study findings can become a steppingstone to further develop an age-friendly city for the ageing population, rejuvenate the city centre through better spatial planning and utilise available city features to maximise social capital building.